Cechy językowe akt stanu cywilnego z lat 1809–1823 parafii myśliborskiej - Osowski, Błażej (Slavia Occidentalis, 2014)
The studied documents of the registry are linked by the time and place of origin as well as the person of the priest Celestyn Zaręba Cielecki – a parish-priest in Myślibórz who signed almost all documents from the discussed period. Nevertheless, on the basis of linguistic and graphical analysis, it has been established that the documents were drafted by as many as 13 different writers. The aim of the article is to present the non-normative features and to try to answer the question whether – on the basis of the linguistic features of the documents – we can determine the place of origin of the writers. Were they the persons representing local dialectic features, i.e., of the eastern Great Poland (Wielkopolska), or they came from other regions?